HIGH RESOLUTION SEAMLESS DOM GENERATION OVER CHANG'E-5 LANDING AREA USING LROC NAC IMAGES - K. Di (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2018)
Chang’e-5, China’s first sample return lunar mission, will be launched in 2019, and the planned landing area is near Mons Rümker in Oceanus Procellarum. High-resolution and high-precision mapping of the landing area is of great importance for supporting scientific analysis and safe landing. This paper proposes a systematic method for large area seamless digital orthophoto map (DOM) generation, and presents the mapping result of Chang’e-5 landing area using over 700 LROC NAC images. The developed method mainly consists of two stages of data processing: stage 1 includes subarea block adjustment with rational function model (RFM) and seamless subarea DOM generation; stage 2 includes whole area adjustment through registration of the subarea DOMs with thin plate spline model and seamless DOM mosaicking. The resultant seamless DOM coves a large area (20° longitude × 4° latitude) and is tied to the widely used reference DEM – SLDEM2015. As a result, the RMS errors of the tie points are all around half pixel in image space, indicating a high internal precision; the RMS errors of the control points are about one grid cell size of SLDEM2015, indicating that the resultant DOM is tied to SLDEM2015 well.